TAMSULOSIN Vs NAFTOPIDIL IN MEDICAL EXPULSIVE THERAPY FOR URETERAL STONES: A RANDOMIZED CONTROLLED STUDY - N. MEENA DEVI; KH. SANIA MONICA; M. MEDHABATI DEVI; AK. KAKU SINGH (International Journal of Pharma and Bio Sciences, 2014)
The aim of the present study was to compare the efficacy of tamsulosin and naftopidil in the management of ureteral stones in Regional Institute of Medical Sciences, Imphal. A total of 92 patients with symptomatic, single ≤ 10 mm ureteral stone, were enrolled in a prospective study and randomized into two groups. Group 1, received 0.4 mg tamsulosin daily, whereas Group 2, received 50 mg naftopidil daily. Patients were followed – up for up to 6 weeks. The primary end point was stone expulsion rate and secondary end points were stone expulsion time, the rate of interventions such as uretero-renoscopy, ureteric stenting and extracorporeal shock wave lithotripsy and side effects. There were no significant differences between the groups with respect to age, sex, stone size and location. Stone expulsion rate were 76% and 56% in the tamsulosin and naftopidil group respectively. No significant difference in the stone expulsion time and the rate of interventions between the two groups. The findings suggest that tamsulosin is superior to naftopidil for stone expulsion therapy.